Pengaruh Harga, Citra Merek Dan Gaya Hidup Terhadap Keputusan Pembelian Hijab Bella Square Di Kalangan Mahasiswa FEBI UINSU - Nailul Muna; Tuti Anggraini; Atika (CV. ITTC INDONESIA, 2023)
This study aims to statistically prove the effect of price, brand image and lifestyle on purchasing decisions for Bella Square hijab among FEBI UINSU students. The sample method used in this study uses the formula hair, et al. The sample in this study were students who often buy or use Bella Square hijabs with a total of 75 people. The primary data obtained were analyzed by using multiple linear regression analysis through the IBM SPSS Statistics 25 program. The results of this study indicate that price has a significant effect on buyer decisions with a t-value of 2.074 > 1.6666, a significance of 0.002 <0.05. Brand image has a significant effect on buyer decisions with a t-value of 3.361 > 1.6666, a significance of 0.019 <0.05. Lifestyle has a significant effect on buyer decisions with a t-value of 2.011 > 1.6666, a significance of 0.001 <0.05. Price, brand image and lifestyle simultaneously have a significant effect on purchasing decisions for Hijab Bella Square among FEBI UINSU students with an f count of 11,581 > 2.73 with a significance of 0.001 <0.05.